2019
DOI: 10.1044/2018_jslhr-s-18-0205
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physiological Mechanisms and the Self-Perception of Vocal Effort

Abstract: Purpose This study aimed to examine the relationship between a large set of hypothesized physiological measures of vocal effort and self-ratings of vocal effort. Method Twenty-six healthy adults modulated speech rate and vocal effort during repetitions of the utterance /ifi/, followed by self-perceptual ratings of vocal effort on a visual analog scale. Physiological measures included (a) intrinsic laryngeal tension via kinematic stiffness ratios determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…A subsequent analysis of the same participants from McKenna and Stepp 29 further revealed that increased subglottal pressure estimates, medial supraglottic compression, and increased activation of suprahyoid muscles were significantly related to the self-perception of vocal effort. 28 The authors suggested that the physiological basis of vocal effort may, in fact, overlap with the symptoms of those with increased laryngeal tension and/or hyperfunctional vocal behavior. This hypothesis falls in line with the research by Remacle et al, 21 which found that a subset (9%) of their participants exhibited acoustic responses to occupational loading that were consistent with increased glottal adduction (ie, increased HNR with simultaneous reduction in shimmer).…”
Section: Acoustic Measures Of Vocal Effort and Laryngeal Tensionmentioning
confidence: 99%
“…A subsequent analysis of the same participants from McKenna and Stepp 29 further revealed that increased subglottal pressure estimates, medial supraglottic compression, and increased activation of suprahyoid muscles were significantly related to the self-perception of vocal effort. 28 The authors suggested that the physiological basis of vocal effort may, in fact, overlap with the symptoms of those with increased laryngeal tension and/or hyperfunctional vocal behavior. This hypothesis falls in line with the research by Remacle et al, 21 which found that a subset (9%) of their participants exhibited acoustic responses to occupational loading that were consistent with increased glottal adduction (ie, increased HNR with simultaneous reduction in shimmer).…”
Section: Acoustic Measures Of Vocal Effort and Laryngeal Tensionmentioning
confidence: 99%
“…However, there were no movement pattern differences with vocal onsets and offsets between subjects with and without pMTD using optical flow analysis for either suprahyoid or infrahyoid muscles. The lack of group differences using objective and quantifiable methods like optical flow to study phonatory paralaryngeal movement patterns in the suprahyoid and infrahyoid muscle groups challenges clinical wisdom that vocal hyperfunction in the paralaryngeal muscles occurs and contributes to vocal dysfunction in patients with pMTD, [1][2][3]10,11,14,15 at least at modal pitch and loudness.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, avoiding compensatory strain is at least a secondary target of most voice therapy regimens [ 63 – 67 ]. In addition, avoiding compensatory strain could be beneficial over an extended period of time, whereas vocal strain might quickly lead to negative vocal symptoms [ 68 , 69 ]. This finding could, in part, be related to the type of vocal exertion task used in this study.…”
Section: Discussionmentioning
confidence: 99%